What's new in tuberculosis vaccines? - Ann M. Ginsberg
Over the past 10 years, tuberculosis (TB) vaccine development has resurged as an active area of investigation. The renewed interest has been stimulated by the recognition that, although BCG is delivered to approximately 90% of all neonates globally through the Expanded Programme on Immunization, Mycobacterium tuberculosis continues to cause over 8 million new cases of TB and over 2 million deaths annually. Over one hundred TB vaccine candidates have been developed, using different approaches to inducing protective immunity. Candidate vaccines are typically screened in small animal models of primary TB disease for their ability to protect against a virulent strain of M. tuberculosis. The most promising are now beginning to enter human safety trials, marking real progress in this field for the first time in 80 years.